Safety behaviour and safety management : a system dynamics modelling of safety rule violation behaviour (SRVB) in a high-risk mining system - Mariri, Tendai (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.